The New Deal: A Potential Role for Secreted Vesicles in Innate Immunity and Tumor Progression - Benito-Martin, Alberto; Di Giannatale, Angela; Ceder, Sophia; Peinado, Héctor (Frontiers in Immunology, 2015)
Tumors must evade the immune system to survive and metastasize, although the mechanisms that lead to tumor immunoediting and their evasion of immune surveillance are far from clear. The first line of defense against metastatic invasion is the innate immune system that provides immediate defense through humoral immunity and cell-mediated components, mast cells, neutrophils, macrophages and other myeloid-derived cells that protect the organism against foreign invaders. Therefore, tumors must employ different strategies to evade such immune responses or to modulate their environment, and they must do so prior metastasizing. Exosomes and other secreted vesicles can be used for cell-cell communication during tumor progression by promoting the horizontal transfer of information. In this review, we will analyze the role of such extracellular vesicles during tumor progression, summarizing the role of secreted vesicles in the crosstalk between the tumor and the innate immune system.